h - Mezini, Mira.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 25th European Conference on Object-Oriented Programming, ECOOP 2011, held in Lancaster, UK, in July 2011. The 26 revised full papers, presented together with three keynote lectures were carefully reviewed and selected from a total of 100 submissions. The papers cover topics such as empirical studies, mining, understanding, recommending, modularity, modelling and refactoring, aliasing and ownership; as well as memory optimizations.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Information Systems; Computer Science; Programming Techniques; Software Engineering; Programming Languages, Compilers, Interpreters; Logics and Meanings of Programs; Computer Communication Networks; Management of Computing and Information Systems